ANALYSIS OF FARMERS’ COMMUNICATION NETWORK IN REPLANTING OIL PALM IN TRI MULYA JAYA VILLAGE - Wiari Zhuhuri; Roza Yulida; Yulia Andriani (Universitas Sebelas Maret, 2026)
This research aims to understand the communication network in the context of independent oil palm cultivation in Tri Mulya Jaya Village. Through interviews and questionnaires involving 15 oil palm farmers, the study utilized non-probability sampling methods such as purposive and snowball sampling. The results indicated internal and external conditions supporting the adoption and implementation of oil palm cultivation. Factors like productive age, upper secondary education, and moderate land area collaborated with the effectiveness of extension officer visits and income levels. The farmers' use of smartphones reflected the effectiveness of agricultural extension. The communication network pattern formed a circular structure with equal roles and strengths, promoting optimal participation. Central figures, particularly HN and AS, played a key role in information dissemination. Despite JM having the highest closeness, the centrality of HN and AS marked popularity in the communication network. Centrality analysis highlighted the central role of association figures in supporting oil palm replanting activities. Communication patterns and functional relationships played a crucial role in forming an effective network in Tri Mulya Jaya Village.